The second Team Haemophilia Education Meeting, 2016, Frankfurt, Germany. (January 2017) - Berntorp, Erik; Dargaud, Yesim; Hart, Daniel; Lobet, Sébastien; Mancuso, Maria Elisa; d'Oiron, Roseline; Perry, David; Pollard, Debra; van den Berg, Marijke; Blatný, Jan; Chambost, Hervé; Doria, Andrea S.; et al.
Abstract: The first Team Haemophilia Education (THE) Meeting was held on 7–8 May 2015 in Amsterdam, The Netherlands. It aimed to promote the optimal care of patients with haemophilia through education of the multidisciplinary treatment team. This was achieved by reviewing the latest developments in haemophilia management, considering how these can be implemented in the clinic to improve patient care and providing a platform for networking and debate for all haemophilia treatment team members. The second THE Meeting was held on 19–20 May in Frankfurt, Germany, and participants included doctors, nurses, physiotherapists, patient representatives and data management staff from 20 different countries. Topics covered the role of the multidisciplinary team in delivering the best haemophilia care, challenges in the management of haemophilia across Europe, available clotting factor treatments, future treatments and the use of genetics in advising carriers of haemophilia. This report is a summary of the key developments in haemophilia care presented by various investigators and healthcare professionals at THE Meeting 2016.